1968
DOI: 10.1139/m68-192
|View full text |Cite
|
Sign up to set email alerts
|

Chemotaxonomic and ultrastructural studies on three species of Tilletia occurring on wheat

Abstract: Electron microscopic investigations and chemical analyses were made on the spores of three species of Tilletia. Frozen-etched preparations examined in the electron microscope revealed that the spore walls of both T. foetida (smooth external surface) and T. caries (reticulate surface with some hair-like projections) contain two layers. The spore wall of T. controversa (complex reticulate surface with many hair-like projections) contains three layers. The outer layer in T. controversa has granular regions which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
0

Year Published

1970
1970
1977
1977

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 0 publications
3
4
0
Order By: Relevance
“…Distribution of the total fatty acids in the sporangiospores and mycelia of R. arrhizus shows many similarities. The high concentrations of linoleic acid are consistent with the results of spore analysis of several fungal organisms previously analyzed (5,7,17). The low concentrations of linolenic acid are also consistent with spores previously analyzed (5,17).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Distribution of the total fatty acids in the sporangiospores and mycelia of R. arrhizus shows many similarities. The high concentrations of linoleic acid are consistent with the results of spore analysis of several fungal organisms previously analyzed (5,7,17). The low concentrations of linolenic acid are also consistent with spores previously analyzed (5,17).…”
Section: Discussionsupporting
confidence: 88%
“…The high concentrations of linoleic acid are consistent with the results of spore analysis of several fungal organisms previously analyzed (5,7,17). The low concentrations of linolenic acid are also consistent with spores previously analyzed (5,17). These consistencies remain true even though environmental conditions are different for the mycelia and spore cultures.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although temperature may be controlled within spores, the microenvironment inside is very complex. For example, T. caries teliospores contain a broad range of lipids and seven major free fatty acids, with significant variation in carbon chain length and degree of saturation (11). The presence of water and other cytoplasmic factors also influences the liquid environment.…”
Section: Fig 11 Thin Section Of a Portion Of A Lipid Body Of A Germmentioning
confidence: 99%
“…Preliminary studies by Oró et al (1966) of the spore lipids extracted from the surface of several smut fungi have shown that alkanes, free fatty acids, and fatty acid methyl esters are common. Recent evidence (Laseter, Hess et al, 1968) has suggested that ketones and aromatics may also occur.…”
mentioning
confidence: 99%